2013
DOI: 10.1111/j.1532-950x.2013.12051.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of an ex vivo canine ventral slot model to test the efficacy of a piezoelectric cutting tool for decompressive spinal surgery

Abstract: The PI allowed completion of ventral slots in a significantly shorter time, without an increased incidence of iatrogenic trauma. The right-handed surgeon showed a left-sided aiming bias, regardless of surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 30 publications
2
17
1
Order By: Relevance
“…Our study confirmed that a lateralized disc herniation can be removed trough a ventral slot centered on the midline. These data are consistent with the results of a previous study on ventral slot decompression surgery by Böttcher et al In our study, the dimensions of the ventral slot were smaller than the safe limits recommended: 33% of the vertebral body length and 30–50% of the vertebral body width . Residual extradural compression in our study seemed to be less frequent (57% of cases) when compared to a previous study by Böttcher et al (77% of cases) .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study confirmed that a lateralized disc herniation can be removed trough a ventral slot centered on the midline. These data are consistent with the results of a previous study on ventral slot decompression surgery by Böttcher et al In our study, the dimensions of the ventral slot were smaller than the safe limits recommended: 33% of the vertebral body length and 30–50% of the vertebral body width . Residual extradural compression in our study seemed to be less frequent (57% of cases) when compared to a previous study by Böttcher et al (77% of cases) .…”
Section: Discussionsupporting
confidence: 92%
“…Surgical loupes, the endoscope, and the operative microscope may also prevent the second surgeon from playing a more active role during the surgical procedure. Moreover, the endoscope and the operative microscope are considered to have steep learning curves …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations